RESPONSES OF BLOOD PRESSURE AND HEART RATE IN RATS SUBMITTED TO CHRONIC DEHYDRATION IN EARLY STAGES OF POST-NATAL (Fiep Bulletin - online, 2016)
The purpose of this study was to determine whether the dehydration induced by furosemide in young rats alter the sensitivity to sodium appetite and blood pressure levels (BP) in adulthood. Young Wistar rats (5 and 21 days of life) were submitted to dehydration through furosemide subcutaneous injections (FUR) (10mg/ kg of body mass), control group received subcutaneous administration of saline (NaCl 0, 15M). Induction of dehydration occurred three times a week for five to seven weeks. After treatment period the animals had four weeks for recovery, moreover they were submitted to an induced intake test for water and sodium. During the test, animals were treated individually with injections of subcutaneous FUR. One day after FUR administration, we allowed free access to water and NaCl 0.3 Molar burettes offered in cages. Volume intake was measured during 30 minutes intervals for two hours. After the end of animals test, they were anesthetized with thiopental and prepared for mean arterial pressure (MAP) and heart rate (HR) recorder. We observed after dehydration, in 21 days rats, similar behaviors in both control (N = 13) and the furosemide. Similar results were obtained in animals treated with FUR from the 5th day of life. Furthermore, in FUR treated rats there was an increase in MAP and reduction in HR when compared to the control group. The results demonstrated changes in homeostasis fluid during early post-uterine life. There were no significant changes in sodium appetite. However, sodium appetite appears to be crucial for determining the levels of BP.
Keywords: Sensitivity to Sodium; diuretic; Blood Pressure; Electrolyte control.